2000
DOI: 10.2527/2000.782318x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding value of an enzymatically digested protein for early-weaned pigs.

Abstract: Weanling pigs were used in a series of studies to determine the feeding value of an enzymatically digested protein product developed from a blend of swine and poultry abattoir by-products. The initial study used 156 pigs weaned at approximately 22 d of age to compare the product with menhaden fish meal in Phase II diets. The product supported equal growth rate, and there was no preference for diet exhibited based on inclusion level of the enzymatically digested protein product. The second study used 100 pigs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…amino acid, peptides) for bacterial protein synthesis and some species of bacteria prefer NAN to ammonia-N (Russell et al, 1992; Cruz Soto et al, 1994; Griswold et al, 1996). Lindemann et al (2000) and Dabrowski et al (2003) showed that supplying peptides offered an advantage over free AA that is easily deaminated in the rumen. However, discrepant results were reported from in vitro studies that assessed the effects of peptides on the rumen metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…amino acid, peptides) for bacterial protein synthesis and some species of bacteria prefer NAN to ammonia-N (Russell et al, 1992; Cruz Soto et al, 1994; Griswold et al, 1996). Lindemann et al (2000) and Dabrowski et al (2003) showed that supplying peptides offered an advantage over free AA that is easily deaminated in the rumen. However, discrepant results were reported from in vitro studies that assessed the effects of peptides on the rumen metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Small peptides obtained from proteolytic hydrolysis of different plant proteins have been shown to have various biological and pharmaceutical activities including enhancing growth performance and immunological status (Kotzamanis et al, 2007), offering a more cost-effective way of supplementing AA (Zimmerman et al, 1997; Lindemann et al, 2000; Dabrowski et al, 2003), improving nitrogen retention (Adibi et al, 1993), and increasing mohair fiber growth (Puchala et al, 2002). Zhang et al (2007) reported that feeding or duodenal infusing SSP, improved nitrogen balance and protein biological value and increased digestibility of dietary nutrients in goats and that supplying SSP by infusing through a duodenum fistula was more efficient than feeding.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms may be that: (a) the rate of absorption of small peptides is greater than that of an equivalent amount of free AAs; (b) the rate of catabolism of small peptides by the bacteria of the small intestine is lower than that of an equivalent amount of free AAs; (c) the composition of AAs entering the portal vein is more balanced with the intestinal transport of small peptides than that of individual AAs; (e) provision of functional AAs (e.g., glycine, arginine, glutamine, glutamate, proline, and taurine) to enhance anti-oxidative reactions and muscle protein synthesis [51, 52]; and (e) specific peptides can improve the morphology, motility and function of the gastrointestinal tract (e.g., secretion, motility, and anti-inflammatory reactions), endocrine status in favor of anabolism, and feed intake, compared with an equivalent amount of free AAs. In swine nutrition research, most of the studies involving the addition of peptides to diets have been conducted with post-weaning pigs to improve palatability, growth, health, and feed efficiency [53–58]. This is primarily because young animals have immature digestive and immune systems and weanling pigs suffer from reduced feed intake, gut atrophy, diarrhea, and impaired growth.…”
Section: Introductionmentioning
confidence: 99%
“…As the level of unhydrolyzed leather meal was increased (0, 3, 6, or 9%) in poultry diets gain and feed intake was reduced (Pinheiro et al, 1989). In addition, Lindemann et al (2000) noted that enzymatic treatment improved the quality of protein. However, enzymatic treated skin protein meal fed to layer was rarely reported.…”
Section: Introductionmentioning
confidence: 99%